2003
DOI: 10.1080/14660820310006715
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Voluntary Isometric Contraction: Investigation of Reliability and Learning Effect

Abstract: Maximum Voluntary Isometric Contraction (MVIC) is a standardised, objective and sensitive tool for the measurement of muscle strength. The purpose of this study was to investigate different aspects of reliability of MVIC and to determine if a learning effect existed in a relatively new user of the system. Two clinical investigators participated in the study. The inter- and intra-rater reliability of MVIC of 11 muscle groups was tested on healthy subjects (n=35). Intra-class correlation co-efficients (ICCs) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 9 publications
2
16
1
1
Order By: Relevance
“…Indeed, the execution of an isometric contraction is more common in trained and male subjects compared with the relatively untrained female subjects used in the current investigation. Other research has also shown that a learning effect is present for isometric force testing of relatively inexperienced subjects, with multiple trials required before a reliable result can be established (Bemben et al, 1992;Meldrum et al, 2003). This finding was confirmed in the variation of our MIF data between days (Table 1) and the higher reliability scores achieved after one session of testing (Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, the execution of an isometric contraction is more common in trained and male subjects compared with the relatively untrained female subjects used in the current investigation. Other research has also shown that a learning effect is present for isometric force testing of relatively inexperienced subjects, with multiple trials required before a reliable result can be established (Bemben et al, 1992;Meldrum et al, 2003). This finding was confirmed in the variation of our MIF data between days (Table 1) and the higher reliability scores achieved after one session of testing (Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, when normalized to the mean of the measurements, the relative SEMs for the two studies are similar (10% and 9%, respectively). Meldrum et al [25] used the same QMT measurement system with adults, and the standard error of the difference between test and retest reported can be used to compute the relative SEM: the relative SEM was between 3.9 and 12.8% in adults, to be compared to 9.8 to 15.1% for children in our study. This suggests lower reliability of strength measurement in children than adults possibly due to their poorer concentration or motivation through successive visits.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Scott et al demonstrated for hip flexion and extension fair to good (0.65 – 0.87) inter-rater reliability assessed with a handheld dynamometer and poor to good (0.48 – 0.91) inter-rater reliability assessed with a portable dynamometer anchoring station [ 19 ]. Also a fair to good intra-rater reliability (0.76 – 0.98) for hip and knee flexion and extension movement with a slightly lower inter-rater reliability (0.64 – 0.97) was reported using a strain gauge [ 2 ]. Using isokinetic dynamometry to measure isometric muscle force mainly results in good reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle force testing is a well established method of assessing muscle function in subjects with neurological movement disorder (NMD) [ 1 , 2 ], despite the fact that these tests are in generally not sensitive enough to assess the force of a single muscle. Isometric force measurements are widely used because walking ability has been shown to be related to muscle strength [ 3 - 6 ].…”
Section: Introductionmentioning
confidence: 99%